Penerapan Hukum Pidana Oleh Kepolisian Dalam Penanggulangan Kejahatan Cyberpornography - Siringoringo, Jomastin Hegel (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2023)
This research aims to determine the extent of criminal law regulation in the prevention of cyberpornography crime in Indonesia and the application of criminal law carried out by the police in the process of Investigation and action to overcome. This study uses normative legal research methods, which are descriptive and applied by using primary legal materials and secondary legal materials analyzed by deductive logic reasoning method. The technique of collecting legal materials used is the study of literature. This study also inventoried various laws and regulations, namely the Criminal Code, Telecommunications Law, broadcasting Law, Film law, Press Law, ITE Law and pornography law. In anticipating the crime of cyberpornography, investigators use the legal instruments of the ITE Law and the pornography law for a temporary period of time because in Indonesia there is no legislation that regulates this crime comprehensively and expressively verbist.